Optimalisasi Badan Penasehatan Pembinaan dan Pelestarian Perkawinan (BP4) Dalam Mewujudkan Keluarga Sakinah pada Masa Pandemi Covid 19 di KUA Kecamatan Bojong Gede Bogor - Mitha Hartiani; Ahmad Sobari ; Suyud Arief (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
This study aims to find out how the role and function of BP4 in Bojong Gede District in optimizing performance as a marriage preservation institution, as well as to find out what strategies were carried out by BP4 in Bojong Gede district during the covid 19 pandemic in realizing the Sakinah family and to find out what are the inhibiting factors and support faced by BP4 in carrying out its duties and functions as a marriage preservation agency during the Covid 19 Pandemic. The method used in this research is quantitative. Data collection techniques were carried out using interviews, observation or documentation. The results of the study show 1. The roles and functions of BP4 in the KUA of Bojong Gede District are: a. Provide coaching to the bride and groom. b. Opening consultations regarding munakahat and family law. 2. BP4's strategy in realizing a sakinah family during the covid 19 pandemic is to provide guidance and direction for prospective brides to create a sakinah family, conduct material maturation independently, by providing direction and guidance related to 3i subject matter, namely Faith, Science and Sincere, as well as material about 8 family functions. 3. The factors that hinder BP4 in carrying out its duties are: a. Lack of public knowledge of the function of BP4 and lack of information received by the community. b. The composition of the BP4 management is not yet well organized. The factors that support BP4 in carrying out its duties and functions are: a. BP4 is available at the Bojong Gede District Religious Affairs Office. b. Availability of counselor services for married couples who are experiencing problems in domestic life. Keywords: BP4 BojongGede District, KUA BojongGede District.